2006
DOI: 10.1017/s0959270906000499
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive success of the Crested Ibis Nipponia nippon

Abstract: SummaryThe last remaining population of the Crested Ibis Nipponia nippon in the wild was studied in the Qinling Mountains, Yangxian County, Shaanxi Province, central China, over 24 breeding seasons with particular attention being paid to the nesting behaviour and breeding success. The average clutch size varied significantly among years (2.84 ¡ 0.77; n 5 271), suggesting that food abundance, which was distinct in different areas, was indeed a limiting factor. The mean hatching success was 80.2%, and ranged fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 19 publications
1
56
0
Order By: Relevance
“…A spatial attraction (i.e. positive association) was found in Clusters A, B and C. The larger area of winter-flooded rice fields in Clusters B and C may increase the birds' food searching efficiency and reduce their energy consumption, which could, in turn, increase their reproductive fitness [47], [48]. Spatial dependencies were seen at different distances in Clusters A–C, suggesting that the distribution of winter-flooded rice fields is not the only habitat factor that has an effect on where the Crested Ibis choose to nest.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A spatial attraction (i.e. positive association) was found in Clusters A, B and C. The larger area of winter-flooded rice fields in Clusters B and C may increase the birds' food searching efficiency and reduce their energy consumption, which could, in turn, increase their reproductive fitness [47], [48]. Spatial dependencies were seen at different distances in Clusters A–C, suggesting that the distribution of winter-flooded rice fields is not the only habitat factor that has an effect on where the Crested Ibis choose to nest.…”
Section: Discussionmentioning
confidence: 92%
“…Wetlands at low elevations, such as riverbanks, reservoirs and rice field channels, can act as alternative winter habitats and also provide the Crested Ibis with abundant food [51]–[53]. Despite the different dependencies seen for winter-flooded rice fields in their selection of nest sites, no significant variation in the number of successful nests and their breeding success at different altitudes was found [47]. Wang and Li [53] pointed out that the fledging success of the Crested Ibis did not differ between low- and high-elevation habitats.…”
Section: Discussionmentioning
confidence: 99%
“…It is observed that the softly released captive‐born individuals of our focal population, the Tongchuan population (Yu et al unpublished data) and the Sado population (Nagata & Yamagish ), were more faithful to the release sites than others. In addition, supplementary feeding could greatly improve the reproductive success of the wild and reintroduced populations (Yu et al , ). Hence, we recommend soft release and food supplementation should be adopted to keep the released ibises in the vicinity of release site immediately after release.…”
Section: Discussionmentioning
confidence: 99%
“…Their refuge comprised several ancient oaks for nesting and nearby winter-flooded rice fields for foraging (Schaller 1994). Apart from a few records of the historical distribution of this species, previous studies on reproduction (Yu et al 2006), foraging and breeding habitat selection Liu et al 2003), population dynamics and demography (Wang and Li 2008), and conservation strategies (Xi et al 2002;Su 2008) in wild crested ibis have been conducted based on this rediscovered and recovering population. Scientists attributed the dramatic decline of the crested ibis population in the mid-twentieth century to the combined influence of habitat loss (due to changing farming practices) and the high risk of human-induced mortality (due to hunting and use of toxic pesticides) (Li et al 2009;Ding 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly believed that the strict conservation measures combined with a higher public awareness contributed to increased breeding population size and reduced anthropogenic disturbances, which have contributed to the rapid recovery of the crested ibis population (Wang and Li 2008). Given such strict conservation, food availability has been identified as the primary limiting factor to the population growth of the ibis (Xi et al 2002;Yu et al 2006).…”
Section: Introductionmentioning
confidence: 99%